1992
DOI: 10.1071/pp9920449
|View full text |Cite
|
Sign up to set email alerts
|

Mango Sapburn: Components of Fruit Sap and Their Role in Causing Skin Damage.

Abstract: Damage caused to the skin of mango fruit by contact with sap exuded from the cut or broken pedicel reduces consumer acceptance and storage life of the fruit. Mangoes of the Kensington cultivar are particularly susceptible to sapburn injury. On centrifugation, the fruit sap separated into two phases. Skin damage was caused predominantly by the upper non-aqueous phase. A major component of this phase was terpinolene which gave symptoms indistinguishable from sapburn injury when applied to the fruit surface. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 9 publications
6
47
0
Order By: Relevance
“…The storage of terpenoid in these structures can be used to limit the toxicity risk to the plant itself, because it is proven that many terpenoids are potentially toxic to plant tissues when monoterpenes are released to the surrounding cells [20]. Injuries were also found when some sesquiterpenes were artificially deposited on sheets during tests on their ability to deter herbivores [23].…”
Section: Introductionmentioning
confidence: 99%
“…The storage of terpenoid in these structures can be used to limit the toxicity risk to the plant itself, because it is proven that many terpenoids are potentially toxic to plant tissues when monoterpenes are released to the surrounding cells [20]. Injuries were also found when some sesquiterpenes were artificially deposited on sheets during tests on their ability to deter herbivores [23].…”
Section: Introductionmentioning
confidence: 99%
“…However, in cryogenically fixed and microwave-fixed peppermint gland specimens, the fibrillar material appears clearly distinct from the walls. Since monoterpenes can be toxic to plant cells (Shomer and Erner, 1989;Loveys et al, 1992), the hydrophilic material could represent a protective mucilage-containing barrier between the secreted oil and the glandular cap cells. Histochemical staining has shown that, in addition to lipids which form the bulk of the stored secretion, the peltate glands of Salvia aurea (Serrato-Valenti et al, 1997), Salvia blepharophylla (Bisio et al, 1999), andO.…”
Section: Enlargement Of the Sub-cuticular Spacementioning
confidence: 99%
“…Terpinolene was found to be the most abundant compound in the oil fraction at over 80% in KP mango, but it accounted for only 3.33% of the oil fraction in Irwin mango sap (Loveys et al 1992). …”
Section: First Theory On Lenticel Damage Mechanismmentioning
confidence: 99%
“…Sap can potentially leak out of resin ducts and enter lenticels due to high pressure. Laticifiers progressively become closer to the mango fruit surface and adjacent lenticels as the fruit develop (Loveys et al 1992).…”
Section: First Theory On Lenticel Damage Mechanismmentioning
confidence: 99%
See 1 more Smart Citation